Interplay between integrins and PI4P5K Sktl is crucial for cell polarization and reepithelialisation during Drosophila wound healing. - Park, S.H.; Lee, C.W.; Choe, K.M. (Scientific reports, 2019)
Phosphatidylinositol(4,5)-bisphosphate [PI(4,5)P2] regulates cell adhesion and actin dynamics during cell migration. PI(4,5)P2 binds various components of the cell adhesion machinery, but how these processes affect migration of the epithelial cell sheet is not well understood. Here, we report that PI(4,5)P2 and Sktl, the kinase that converts PI4P to PI(4,5)P2, are both localized to the rear side of cells during wound healing of the Drosophila larval epidermis. The Sktl localization requires JNK pathway activation and integrins, but not PVR. The sktl knockdown epidermis displays strong defects in would closure, reminiscent of the JNK-depleted epidermis, and shows severe disruption of cell polarity, as determined by myosin II localization. Sktl and ?PS integrin colocalize at the rear side of cells forming the trailing edge during wound healing and the two are inter-dependent in that the absence of one severely disrupts the rear localization of the other. These results strongly suggest that the JNK pathway regulates the rear localization of Sktl and integrins and the interplay between Sktl and integrins sets up cell polarity, which is crucial for reepithelialisation during wound healing.